Contribution Of Human Civilization Towards The Millennial Era - Maldun, Syamsuddin (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Civilization is the essence of history, passed by a society or a state, which will consciously create dynamics continuously in society. This dynamic at the same time provides space and time for the community or the State to move forward in business and work, and have certain methods in life and give birth to a passionate scientific movement. While the essence of civilization is physical and spiritual progress which includes intelligence and culture with the object of a nation. As imaginary creatures, humans have a dynamic power of movement. With reason, humans are able to make changes, both individually and socially. With reason, humans are able to have a noble degree before their Lord and honorable before humans. Advances in technology continue to grow very rapidly and give birth to a digital society. Changes in human life patterns due to technological advances so that they become more pragmatic, hedonic, secular, and give birth to instant generations but still prioritize effectiveness and efficiency. Technological progress has a double face because it has positive and negative influences on human life. Solutions to suppress and overcome the negative impacts of technological progress in the millennial era can be done by synergizing the roles of family, education, society and the state.